SOME ASPECTS OF ECONOMIC EDUCATION TO PRESCHOOL CHILDREN - Asal A. Urazalieva (European International Journal of Pedagogics, 2023)
Increasing economic literacy of children in preschool educational institutions in world educational organizations and scientific centers, innovative models of developing initial economic knowledge and skills using "Forsite" innovative educational technologies; In Russia, the USA, South Korea, Sweden, Germany, from preschool age, to provide children with basic economic knowledge and education, to develop practical knowledge and skills in economics, entrepreneurship, thrift, money and monetary relations. scientific research is being carried out. At the same time, special attention is being paid to scientific research on modeling the processes of primary economic education, expanding the use of innovative technologies in the formation of economic culture.